Pengaruh Penerapan Manajemen Strategik terhadap Kepuasan Pengunjung : (Studi Kasus di Taman Mini Indonesia Indah) - Heru Budi Santoso; Dedi Muliadi; Joko Setyawan; Wahyu Leman (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to analyze the influence of the implementation of strategic management on visitor satisfaction at Taman Mini Indonesia Indah (TMII). The implementation of strategic management in tourist destinations is crucial in improving the quality of service and visitor attraction, especially in the era of increasingly tight tourism competition. The research method used was quantitative with a simple regression analysis technique, involving 30 respondents who were TMII visitors. The results showed that the implementation of strategic management had a positive and significant influence on visitor satisfaction, with a regression coefficient of 0.75· This value shows that any improvement in the implementation of strategic management will increase visitor satisfaction by 75%. These findings emphasize the importance of implementing a planned and integrated strategy at TMII in order to achieve higher satisfaction for visitors. Thus, this study gives the implication that TMII needs to continue to improve its management strategy to create an optimal and sustainable tourism experience for visitors.